Analisis Projek Penguatan Profil Pelajar Pancasila Dalam Meningkatkan Jiwa Wirausahawan Pada Peserta Didik Fase B UPT SD Negeri 40 Gresik - Nurul Ilmiah; Ismail Marzuki (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
The purpose of this study is to describe and find out contextually how the strengthening of the Pancasila Student Profile Project is implemented in the independent curriculum in the basic description of schools by choosing the theme of entrepreneurship.The researchers employed qualitative research methodologies using a descriptive approach in their study. This research collected data via observation and interviews with teachers and students. The subjects studied were students in UPT SD Negeri 40 Gresik, class 4, and The findings obtained during the process of data collecting are documented and presented in a descriptive manner. The following is what the findings of this study were: 1) an introduction or socialization of the Pancasila Student Profile Strengthening Project; 2) a diagnostic assessment (knowing student characteristics); 3) a study of entrepreneurship material from the start of manufacture, selection, and sales; 4) summative assessment (knowing whether the learning objectives are achieved or not); 5) practical or project studies (celebration of learning outcomes); 6) evaluation and reflection on students.